2015
DOI: 10.1039/c5cc03200h
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of the Cu-SSZ-39 catalyst for DeNOx applications

Abstract: The use of small pore zeolites with large cavities has been reported for relevant applications in catalysis or gas separation.[1] One of the most important applications of these materials as catalysts is the selective catalytic reduction (SCR) of nitrogen oxides (NO x ), where copper-containing zeolites with small pore sizes show excellent activities to remove these hazardous compounds produced during combustion in diesel engines. [1,2] Interestingly, these small-pore zeolites show higher hydrothermal stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 22 publications
1
85
0
2
Order By: Relevance
“…Besides zeolites with the CHA framework structure, we have shown that Cu‐SSZ‐39 zeolite (AEI structure) is an excellent NH 3 ‐SCR catalyst, which in some cases even outperform Cu‐CHA in terms of activity and stability. Thus, it would be expected that Fe‐SSZ‐39 would perform comparatively well as a high‐temperature NH 3 ‐SCR catalyst.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Besides zeolites with the CHA framework structure, we have shown that Cu‐SSZ‐39 zeolite (AEI structure) is an excellent NH 3 ‐SCR catalyst, which in some cases even outperform Cu‐CHA in terms of activity and stability. Thus, it would be expected that Fe‐SSZ‐39 would perform comparatively well as a high‐temperature NH 3 ‐SCR catalyst.…”
Section: Figurementioning
confidence: 99%
“…However, the incorporation of iron within the AEI structure has not yet been described, which is probably due to the fact that this material was only achieved under very limited synthesis conditions and with low solid yields (below 40 %) . Recently, we reported the synthesis of high‐silica SSZ‐39 with improved yields (above 85 %) by means of a zeolite‐to‐zeolite transformation procedure …”
Section: Figurementioning
confidence: 99%
“…[13] In general, well-formed zeolite precursors are described to decompose into small fragments containing characteristic SBUsi nt he synthesis gel when treated hydrothermally,t hus favoring the rearrangement and crystallization of other structures sharing similar SBUs. [15] These zeolite-to-zeolite transformations allow control over the particle sizes,h eteroatom substitutions,o rs olid yields of different zeolites that could not be easily achieved when using other amorphous bulk silica sources. [15] These zeolite-to-zeolite transformations allow control over the particle sizes,h eteroatom substitutions,o rs olid yields of different zeolites that could not be easily achieved when using other amorphous bulk silica sources.…”
Section: Introductionmentioning
confidence: 99%
“…[20,30] This material has been tested for the MTO reaction at 350ºC and WHSV=0.8 h -1 , obtaining an excellent catalytic activity and catalyst lifetime (X 50 =860 min, see SSZ-39_50 nm in Figure 8b). …”
Section: -Comparison Of the Catalytic Activity Of Sapo-18 Materials Wmentioning
confidence: 99%